Citizen Participation in National Policy Formulation: Analysis TNI Law Rejection through Social Media - Werdhani, Lukita; Indryani, Gayatri Widya (Public Policy and Management Inquiry, 2025)
Citizen participation in national policy formulation is important in maintaining democratic sustainability and government legitimacy. However, citizen participation in the policy-making process in Indonesia is still limited, which often leads to social discontent and public protests. Cases of large demonstrations that took place in February and March 2025, such as the #IndonesiaGelap action, show people's dissatisfaction with government policies that are deemed incompatible with their needs, such as the 12% VAT policy and the revision of the TNI Law. The public, who felt ignored by formal channels, began to shift their expression of protest through social media, which allowed them to participate directly in the policy process. This research explores the role of social media as a channel for citizen aspiration in fighting for public policy change in Indonesia by looking at how social media can increase citizen engagement and strengthen government transparency and accountability. Based on the analysis of real cases, social media proved to be an effective channel to accelerate policy change despite challenges related to population bias and information credibility. This research suggests that the government improve the accessibility of citizen participation channels and integrate social media as part of a more inclusive and transparent policy formulation strategy.